Faunal survey of grassland ecosystems in South India (Zoological Records and Reviews, 2023)
South Indian grasslands -- encompassing the Deccan Plateau short-grass savannas, the shola-grassland mosaic of theNilgiri and Palani hills, and the seasonally flooded coastal and riverine grasslands of Andhra Pradesh and Tamil Nadu --support a distinctive and ecologically significant fauna that is threatened by widespread conversion to plantations,afforestation, and agricultural expansion. These grassland types are among the most undervalued and poorlydocumented ecosystems in India, lacking the charismatic large mammal fauna of forests that drives conservationattention, yet supporting diverse communities of grassland specialists including wolves, blackbucks, great Indianbustards, larks, and grassland-associated herpetofauna and invertebrates. This study presents a systematic multi-taxonfaunal survey of 36 grassland sites across three grassland types in South India, using standardised transect counts,camera trapping, and invertebrate sampling during wet and dry seasons over two years (2021-2023). A total of 342animal species from five groups are documented, including 84 grassland-specialist species restricted to open habitats.Grassland area, grazing intensity, and connectivity to other grassland patches are the three strongest predictors ofgrassland-specialist species richness. Eight species are IUCN Threatened, including the Critically Endangered greatIndian bustard (Ardeotis nigriceps). Plantation afforestation, overgrazing, and agricultural conversion are the dominantthreats. Conservation recommendations for South Indian grassland fauna are presented.